Capacity of Local Government Policy in Implementing Minimum Service Standards - Koeswara, Hendri; Aromatica, Desna; Tomimi, Zahran Mabrukah; Liesmana, Roza; Kabullah, Muhammad Ichsan; Puri, Wulan Puspita; Tjenreng, M. Zamzani B. (Journal Public Policy, 2025)
This study analyzes local government policies' capacity to implement Indonesia's Minimum Service Standards (MSS), focusing on enforcing Government Regulation No. 2/2018 and Minister of Home Affairs Regulation No. 59/2021. These policies encompass six sectors: education, health, public works, housing, public order and safety, and social affairs. The findings reveal uneven and fluctuating MSS achievements. Although mandatory spending—20% for education and 10% for health—is in place, it does not consistently lead to improved outcomes. Similarly, fiscal capacity does not always correlate with MSS performance. Using a qualitative method—through interviews, FGDs, observations, and literature review—this study identifies that the policy capacities of individuals, organizations, and political actors influence the achievement of MSS. Among these, political capacity—particularly weak commitment from implementers—emerges as the most significant barrier. The study concludes that a new model and formula within the policy framework is essential to address service disparities and improve performance across all regions to ensure equitable and effective MSS implementation.